Does treatment specific-, disorder specific- or general therapeutic competence predict symptom reduction in posttraumatic stress disorder? - Steil, Regina; Weiß, Judith; Müller-Engelmann, Meike; Dittmann, Clara; Priebe, Kathlen; Kleindienst, Nikolaus; Fydrich, Thomas; Stangier, Ulrich (European journal of psychotraumatology, 2023)
Background: Literature on the association between therapist competence and treatment success in posttraumatic stress disorder (PTSD) treatments is scarce and results are mixed. Aims/Objective: The relationship between different types of therapeutic competence, therapeutic alliance, and PTSD symptom reduction in patients treated with Dialectical Behaviour Therapy for PTSD (DBT-PTSD) or Cognitive Processing Therapy (CPT) was assessed. Competence types were PTSD-specific competence, treatment specific competence, and general competence in cognitive behaviour therapy (CBT). Method: Videotaped therapy sessions from N = 160 women with PTSD and emotion regulation difficulties after child abuse participating in a large randomised controlled trial (Bohus et al., 2020) were rated. Three therapeutic competence-types were assessed using specifically developed rating scales. Alliance was assessed via patient ratings with the Helping Alliance Questionnaire (HAQ). PTSD symptoms were assessed at pre- and post-treatment via clinician rating with the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) and via self-rating with the PTSD-Checklist for DSM-5 (PCL-5). Results: No significant association between competence and clinician or self-rated PTSD symptoms was found. PTSD specific competence predicted clinician rated PTSD symptom severity on a trend level. Alliance predicted both clinician and self-rated PTSD symptom reduction. Conclusion: Our results provide a starting point for future research on different competence types and their association with PTSD treatment gains. Therapists were highly trained and received weekly supervision, hence a restricted competence range is a possible explanation for non-existing associations between competence and PTSD symptom reduction in our sample. More research in naturalistic settings, such as dissemination studies, is needed. Three different types of therapeutic competence and their association to treatment gains in women with posttraumatic stress disorder after child abuse were assessed.Therapist competence was high in all three domains of competence.No association was found between any of the competence types and reduction in posttraumatic stress disorder symptoms.